2015
DOI: 10.1039/c5ra02870a
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the high reactivity of commercial Fe–Si–B amorphous zero-valent iron in degrading azo dye solutions

Abstract: Improving intrinsic reactivity is one of the key requirements in applying zero-valent iron in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 34 publications
(40 reference statements)
1
39
0
Order By: Relevance
“…Since ribbon samples are beneficial to the experimental operation, the degradation mechanism of MG were also investigated based on the ribbons. Most related reports have demonstrated that the degradation efficiency is greatly deteriorated after annealing treatment due to the disappearance of residual stress and metastable structure [1,5,6,12]. However, several recent reports have shown that the chemical heterogeneity of nanocrystals caused by annealing may be beneficial for the degradation of azo dyes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since ribbon samples are beneficial to the experimental operation, the degradation mechanism of MG were also investigated based on the ribbons. Most related reports have demonstrated that the degradation efficiency is greatly deteriorated after annealing treatment due to the disappearance of residual stress and metastable structure [1,5,6,12]. However, several recent reports have shown that the chemical heterogeneity of nanocrystals caused by annealing may be beneficial for the degradation of azo dyes.…”
Section: Introductionmentioning
confidence: 98%
“…Different fabrications usually induce different statuses of MG products, which may strongly affect the efficiency of the MG. Powders, glassy thin films [4] or melt-spun ribbons [5][6][7] are also used in water treatments. Melt spinning is a widely used technology in typical industrial fields [8,9], and thus the ribbons are easy to fabricate.…”
Section: Introductionmentioning
confidence: 99%
“…The lower corrosion potentials of NP powders in azo dye solutions imply that NP powders exhibit higher electrochemical activity, accompanied with more active catalytic activity during the process of degradation with a lower activation energy. Another reason is that the coexistences of the residue amorphous phase in metastable state and metalloid elements such as Si, B and P after dealloying may enhance the catalytic activity of degradation reaction more by forming loose metalloid-containing intermediate products [8]. Here, the excellent catalytic activity of amorphous electrodes results from the abundance of the active sites induced by the special electronic structure [25].…”
Section: Resultsmentioning
confidence: 99%
“…Rapid decay of the degradation efficiency of the iron powders occurs due to the ready rusting, which restricts the extensive utilization in degrading azo dyes. The degradation efficiency of iron based amorphous alloys in decomposing azo dyes is much higher than that of the crystalline ZVI due to its amorphous structure and the addition of metalloids [7,8,9]. Moreover, a series of research works have been conducted to improve the reactivity of these zero-valent iron materials, such as by improving the specific surface area of iron powders (nanoscale ZVI (NZVI) [10,11]), doping with additional metals (such as Pd [4,12], Ni [13], and Cu [14]) and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation